Computerized morphometric assessment of the effect of low level laser therapy on osseointegration of immediate implants with guided bone regeneration - Mahmoud Sayed Hamed; Ali Mohamed Elhoseny Saafan; Gamal Mohamed Moutamed; Khairy Abdelhamied Elmorsy (Cairo : Mahmoud Sayed Hamed, 2012)
This study was conducted in an attempt to evaluate the effect of the low level laser therapy on the bone healing of immediate dental implants . Eleven implant were plased immediately in freshly extracted sockets or traumatic tooth loss in place of irrestorable maxillary central incisors in ten patients , control group (five implants) and laser group (six implants) , the patients of both group received the suitable implant augmented by Biocollagen membrane
Thesis (M.Sc.) - Cairo University - Faculty of Oral and Dental Medicine - Department of Oral and Maxillofacial Surgery
Issued also as CD
Keywords: Collagen membrane; Immediate implant; Low level laser